2008
DOI: 10.1016/j.immuni.2008.07.011
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor PLZF Directs the Effector Program of the NKT Cell Lineage

Abstract: Summary The transcriptional control of CD1d-restricted NKT cell development has remained elusive. We report that PLZF (promyelocytic leukemia zinc finger; Zbtb16), a member of the BTB/POZ-ZF family of transcription factors which includes the CD4 lineage-specific c-Krox (Th-POK, Zbtb7b), is exquisitely specific to CD1d-restricted NKT cells and human MR1-specific MAIT cells. PLZF was induced immediately after positive selection of NKT cell precursors and PLZF-deficient NKT cells failed to undergo the intrathymic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

36
806
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 648 publications
(842 citation statements)
references
References 54 publications
36
806
0
Order By: Relevance
“…BCL6 is expressed at high levels in germinal center B cells 9 and T follicular helper cells 10 that together control the germinal center response. Promyelocytic leukemia zinc finger (ZBTB16) is required for natural killer T-cell development 11 and expression of promyelocytic leukemia zinc finger has recently been shown to identify a multipotent progenitor of innate lymphoid cells. 12 T H -inducing POZ/Kruppel-Like factor (ThPOK, ZBTB7B) is a master regulator of T H -cell development in the thymus.…”
Section: Introductionmentioning
confidence: 99%
“…BCL6 is expressed at high levels in germinal center B cells 9 and T follicular helper cells 10 that together control the germinal center response. Promyelocytic leukemia zinc finger (ZBTB16) is required for natural killer T-cell development 11 and expression of promyelocytic leukemia zinc finger has recently been shown to identify a multipotent progenitor of innate lymphoid cells. 12 T H -inducing POZ/Kruppel-Like factor (ThPOK, ZBTB7B) is a master regulator of T H -cell development in the thymus.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,7,9,11 Recently, an intriguing role of PLZF in immune system has been described. 16,17 Innate T cells bridges the innate and adaptive immune systems, including gdT cells and several subsets of abT cells. In general, innate T cells (of an ab T-cell lineage) develop in the thymus from double-positive progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…27 PLZF is essential for the development of invariant NKT cells with acquisition of their unique innate-like properties in a mouse system. 16,17 Recently, our group and others have reported a new distinct subset of innate abT cells (T-T CD4 T cells), which are selected by MHC class II-expressing thymocytes and also depend on PLZF for their development. [28][29][30] Moreover, we reported that the generation of T-T CD4 T cells is a physiological process in humans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations